Prediction of Propeller Performance Using Quasi-Continuous Method - Rui, Hao; Koto, Jaswar (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
This research is targeted to apply the numerical method in the ship’s propeller design and analysis. In this thesis, the Quasi Continuous Method developed based on lifting surface theory is applied to predict the performance of propeller in open water condition. To fulfill the desire of industry to obtain an accurate, fast and low cost solution in propeller design, this design and analysis process is proposed made by computer programming software. This is because fast development on computer technology provided the possibility to carry propeller design task by using numerical software. In this research, the Quasi Continuous Method for propeller performance evaluation is applied. This method allows the fast propeller prediction process and low computer cost required. In this research, the VLCC ship model and it propulsion system is preselected. The propeller of the VLCC ship is designed and analyzed using the propeller database system in the numerical software OCARI S-Power. Next, the function of Quasi Continuous Method in the software is applied to predict the open water performance of the designed propeller. Finally, the appropriate propeller model and it dimension is determined in this research. In conclusion, application of numerical software in propeller design is an advance solution where this solution is relatively high efficient compare to the traditional method.